Adult Onset Still’s Disease Presenting with Tuberculous Bronchopneumonia: A Case Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2020)
Introduction: The occurrence of Post primary Tuberculosis [TB] can be due to reactivation of previous infection or reinfection. Reactivation of TB could occur due to many conditions including immunosuppressive drug therapy and immunosuppressive diseases. In countries where latent TB is common a good vigilance is needed for early detection of TB when such conditions are managed.Adult onset Still’s disease (AOSD) is a rare systemic disorder of unknown etiology where fever, rash, lymphadenopathy and multi organ involvement occur. ASOD is a challenging condition to diagnose as there are no pathognomonic physical signs or markers. Early diagnosis and initiation of treatment is important as diagnostic delays could lead to serious consequences.Occurrence of tuberculosis in a patient with AOSD has not been documented in literature to-date. Here we describe a 46-year-old male who presented with low grade fever and arthralgia for more than one month with organomegaly and pericardial effusion managed as AOSD, later developed Tuberculous bronchopneumonia.